Environmental and socio-cultural impacts of glyphosate-based herbicides: perspectives from indigenous knowledge and western science - Patterson, Heather; Bowles, Ella; Chiblow, Susan; McGregor, Deborah; Kozmik, Cory; Popp, Jesse (Frontiers in Conservation Science, 2023)
For decades, herbicide application in commercial forestry has been a serious concern for First Nations across northern Ontario. To date, the vast majority of studies concerning the impacts of glyphosate-based herbicides have been conducted through a Western scientific lens. Indigenous knowledge systems provide holistic frameworks which acknowledge the interconnectedness of the environment and provide a holistic view of relationships between flora, fauna, environment, and humans. This socio-ecological perspective is key to understanding the wide-ranging impacts of commercial forestry on the wellbeing of Indigenous Peoples. Through a knowledge sharing workshop, “Connecting Guardians in a Changing World”, we interviewed community members from First Nations across the Robinson-Huron Treaty Area and asked them to share their knowledge and concerns regarding herbicide use in commercial forestry. Based on the topics discussed in these interviews, we conducted a literature review to further investigate documented Western scientific evidence related to concerns raised by workshop participants. We then wove Indigenous Knowledge and Western Science together to identify key concerns of participants regarding the use of glyphosate-based herbicides, identify gaps in current knowledge, and to direct future research. We identified three main research gaps regarding glyphosate-based herbicide impacts used in forestry: 1) research regarding the direct effects of glyphosate-based herbicide toxicity to most of the fauna and flora of the Great Lakes region of northeastern Ontario as well as its environmental persistence, 2) research regarding the indirect effects of glyphosate-based herbicides to the ecosystem and resulting impacts of trophic cascades, and 3) research regarding the impacts of glyphosate-based herbicides to Indigenous culture and community wellbeing. By weaving knowledge systems, we can conduct research based on an inclusive system which prioritizes the inclusion of multiple ways of knowing and which addresses environmental concerns in holistic and inclusive ways which emphasize the interconnectedness of the environment, including humans therein.